MicroRNA Regulation for Inflammasomes in High Glucose-Treated ARPE-19 Cells - Ji Hong Kim; Hyoseon Yu; Ji Hye Kang; Eun Hee Hong; Min Ho Kang; Mincheol Seong; Heeyoon Cho; Yong Un Shin (Journal of Ophthalmology)
Purpose. This study aimed to evaluate the expression of microRNAs (miRNAs) and inflammasomes in diabetes-induced retinal cells and to determine their role in the pathogenesis of diabetic retinopathy (DR). Methods. To establish diabetes-induced cell models, ARPE-19 cells were treated with high glucose. The expression levels of five miRNAs (miR-185, miR-17, miR-20a, miR-15a, and miR-15b) were measured in high glucose-treated ARPE-19 cells using real-time quantitative polymerase chain reaction. Western blotting was performed to measure inflammasome expression in cellular models. miR-17 was selected as the target miRNA, and inflammasome expression was measured following the transfection of an miR-17 mimic into high glucose-treated ARPE-19 cells. Results. In high glucose-treated ARPE-19 cells, miRNA expression was substantially downregulated, whereas that of inflammasome components was significantly increased. Following the transfection of the miR-17 mimic into high glucose-treated ARPE-19 cells, the levels of inflammasome components were significantly decreased. Conclusions. This study investigated the relationship between miRNAs and inflammasomes in diabetes-induced cells using high glucose-treated ARPE-19 cells. These findings suggested that miR-17 suppresses inflammasomes, thereby reducing the subsequent inflammatory response and indicating that miRNAs and inflammasomes could serve as new therapeutic targets for DR.